Edutainment: The essential element in agriculture mechanization - Mat Atar, Mat Amin; Nashriyah, Mat; Mohd Hudzari, Haji Razali (Universiti Teknikal Malaysia Melaka, 2016)
This study was also done to develop virtual teaching tractor as an interactive learning program for students especially for an Agricultural Mechanization subject. The study was divided into two parts which is to develop visual tractor and virtual tractor as a teaching’s tool. The development of this teaching tractor will gives benefits to students. The actual tractor is attractive teaching tractor and virtual tractor Edutainment as interactive teaching tractor. The virtual tractor which is in graphic multimedia will attract students to explore and learn more about the tractor. The virtual tractor Edutainment is the combination of multimedia element which is graphic and interactivity, it will attracts students to learn and explore more about the specifications and all about the parts of tractor. This study also was conducted to explore the accessibility of the virtual tractor Edutainment to link and publish through internet.